A web‐based virtual laboratory for electron probe microanalysis. Issue 4 (16th January 2015) - Lu, Xia; Tian, Di; He, Yu‐Tong; Yao, Li; Fan, Run‐Long
ABSTRACT This paper introduces a novel web‐based virtual laboratory to support teaching electron probe microanalysis (EPMA), specifically operations of the instrument. The virtual lab includes favorable animations to facilitate understanding characteristics of EPMA, the virtual experimental platform for instructive simulations, and quizzes to measure the students' achievements in learning. To illustrate the instrumental operations, typical experimental processes have been simulated with 3 modules and 34 windows. Students responded to the survey that the virtual lab was very effective in promoting understanding of EPMA and helping them to familiarize with the operations of the instrument and improve the skills before performing the experiment in real lab. © 2015 Wiley Periodicals, Inc. Comput Appl Eng Educ 23:489–498, 2015; View this article online at wileyonlinelibrary.com/journal/cae; DOI 10.1002/cae.21620